コクリツ キョクチ ケンキュウジョ ニ セッチ サレタ ソクチ キジュン テン - 板橋, 昭房; イタバシ, アキフサ; 米渓, 武次; コメタニ, タケジ; 渋谷, 和雄; シブヤ, カズオ; Itabashi, Akifusa; Kometani, Takeji; Shibuya, Kazuo (1986)
P(論文) 1985年9月, 国立極地研究所管理・資料棟屋上に測地基準点を設置した。三等三角点下板橋および王子からの測距, 測角により, 国立極地研究所本点の経緯度座標を網平均により求めた。海抜高度は一等水準点017-009から管理・資料棟ベンチマークまでの直接水準測量と鋼巻尺による棟の高低差測定から求めた。観測は国土地理院基準点測量作業規程に準じて実施した。得られた基準点成果は北緯35°45′1.801″, 東経139°43′12.763″, 標高43.25mである。なおNNSS衛星など, 人工衛星受信観測のためのアンテナ設置点として屋上に補助点A, Bをもうけた。 A geodetic control point (named NIPR main-point) was installed in September 1985,on the roof of the Administrative Building of the National Institute of Polar Research. The geodetic coordinates are obtained by measuring distances and angles from the third-order triangulation points Shimo-Itabashi and Oji, and the net adjustment method is applied. The height of NIPR main-point is determined from the levelling between the first-order levelling point 017-009 and the bench mark of the Administrative Building, and the height difference measurement between the roof and the bench mark by using a metal measure. The above observations were made according to the standard operating procedure of the Geographical Survey Institute, Ministry of Construction. The obtained coordinates are 35°45′1.801″N for latitude, 139°43′12.763″E for longitude and 43.25m for height above mean sea level. In order to make satellite receiving experiments, supplementary points A and B are also installed on the roof for antenna location. departmental bulletin paper